Comparison of keypads and touch-screen mobile phones/devices as potential risk for microbial contamination - Koroglu, Mehmet; Gunal, Selami; Yildiz, Fatma; Savas, Mehtap; Ozer, Ali; Altindis, Mustafa (The Journal of Infection in Developing Countries, 2015)
Introduction: Touch-screen mobile phones/devices (TMPs/Ds) are increasingly used in hospitals. They may act as a mobile reservoir for microbial pathogens. The rates of microbial contamination of TMPs/Ds and keypad mobile phones (KMPs) with respect to different variables including use by healthcare workers (HCWs)/non-HCWs and the demographic characteristics of users were investigated. Methodology: A total of 205 mobile phones/devices were screened for microbial contamination: 76 devices belonged to HCWs and 129 devices belonged to the non-HCW group. By rubbing swabs to front screen, back, keypad, and metallic surfaces of devices, 444 samples were collected. Results: Of 205 mobile phones/devices, 143 (97.9%) of the TMPs/Ds and 58 (98.3%) of the KMPs were positive for microbial contamination, and there were no significant differences in contamination rates between these groups, although TMPs/Ds had significantly higher microbial load than KMPs (p <0.05). The significant difference in this analysis was attributable to the screen size of mobile phones ≥ 5”. Microbial contamination rates increased significantly as phone size increased (p <0.05). Higher numbers of coagulase-negative Staphylococci (CNS) were isolated from KMPs than TMPs/Ds (p = 0.049). The incidence of Enterococcus spp. was higher on the KMPs of HCWs, and methicillin resistant CNS was higher from the TMPs/Ds of non-HCWs (p <0.05). Isolation of CNS, Streptococcus spp. and Escherichia coli was higher from the TMPs/Ds of HCWs (p <0.05). Conclusions: We found no significant difference between TMP/Ds and KMPs in terms of microbial contamination, but TMP/Ds harboured more colonies and total microbial counts increased with screen size.